How a Model of Communication Can Assist Nurses to Foster Hope When Communicating with Patients Living with a Terminal Prognosis - Petley, Rebecca (Religions, 2017)
Nurses play a central role in joint decision-making and person-centred care, whereby care is focused on the needs of an individual patient. A key part of person-centred care is the way nurses engage with patients because good communication can impact on a person's spiritual wellbeing, particularly in relation to their ability to have hope. The way nurses communicate can be even more pertinent for people living with a terminal prognosis as the issues discussed can in themselves significantly influence a person's spiritual wellbeing. This paper combines contemporary research on how health professionals can foster hope in patients living with a terminal prognosis with The Awareness Context Theory described by Glaser and Strauss in 1965. A model of communication is then used to demonstrate how the research on hope and The Awareness Context Theory can be applied to practice.